2022
DOI: 10.15252/emmm.202114121
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐8 in endothelial cells maintains gut homeostasis and prevents small bowel inflammation in mice

Abstract: The gut has a specific vascular barrier that controls trafficking of antigens and microbiota into the bloodstream. However, the molecular mechanisms regulating the maintenance of this vascular barrier remain elusive. Here, we identified Caspase‐8 as a pro‐survival factor in mature intestinal endothelial cells that is required to actively maintain vascular homeostasis in the small intestine in an organ‐specific manner. In particular, we find that deletion of Caspase‐8 in endothelial cells results in small intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…However, as resident cell types within the gastrointestinal wall cooperatively maintain gut shape and function [ 49 ], it stands to reason that endothelial defects also precipitate inflammatory gut disease. Indeed, upon completion of our study, another group has separately reported that loss of endothelial Caspase-8 in adult mice precipitates small intestinal hemorrhage [ 50 ]. Our findings largely overlap or extend the observations of Tisch and colleagues [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as resident cell types within the gastrointestinal wall cooperatively maintain gut shape and function [ 49 ], it stands to reason that endothelial defects also precipitate inflammatory gut disease. Indeed, upon completion of our study, another group has separately reported that loss of endothelial Caspase-8 in adult mice precipitates small intestinal hemorrhage [ 50 ]. Our findings largely overlap or extend the observations of Tisch and colleagues [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, upon completion of our study, another group has separately reported that loss of endothelial Caspase-8 in adult mice precipitates small intestinal hemorrhage [ 50 ]. Our findings largely overlap or extend the observations of Tisch and colleagues [ 50 ]. For instance, while polymicrobial products broadly trigger hemorrhage in C8-endo mice, we find that endogenous TLR4-signaling is especially critical for this necroptotic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, it also represents the molecular switch that controls apoptosis, necroptosis and pyroptosis 33 . Caspase-8 has been identi ed to be a pro-survival factor for gut epithelial cells 34 and mature gut endothelial cells 22 . Caspase-8 is required to actively maintain vascular homeostasis in small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-8 is required to actively maintain vascular homeostasis in small bowel. Thus, loss of caspse-8 in gut endothelial cells leads to gut hemorrhages, in ammation, and GVB hyper-permeability to FITC-dextran 70 kDa 22 . Caspase-8 de ciency also causes embryonic lethality in mice 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, CASP8-deficient enterocytes displayed decreased in vivo survival and migration potential [ 1483 ]. Specific deletion of Casp8 in endothelial cells results in small intestinal hemorrhage and bowel inflammation, suggesting a key role of CASP8 in vascular homeostasis in the small intestine [ 1484 ]. Loss of CASP8 catalytic activity specifically in intestinal epithelial cells induced intestinal inflammation similar to absence of CASP8 in the intestinal epithelium [ 1424 ].…”
Section: Extrinsic Apoptosis In Diseasementioning
confidence: 99%